2004
DOI: 10.1143/jjap.43.3636
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion and Purification of Single-Wall Carbon Nanotubes Using Carboxymethylcellulose

Abstract: We have developed a novel method for the purification of single-wall carbon nanotubes (SWNTs) that involves annealing in air and dispersing the SWNTs in an aqueous solution of carboxymethylcellulose (CMC). The purity of the resulting SWNTs was evaluated by analytical techniques such as electron microscopy, Raman spectroscopy, and thermogravimetric analysis (TGA). As a result, it was revealed that CMC functioned as an effective dispersion reagent in the exfoliation of the SWNT bundles and thereby, SWNTs with ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 22 publications
2
70
1
Order By: Relevance
“…on the SWNT sidewalls. [62,63,106,201,[231][232][233][234] This gives little or no change in electronic properties. [235] A number of polymers have recently been used to disperse SWNTs in non-aqueous media.…”
Section: Dispersion Of Nanotubes In Solventsmentioning
confidence: 99%
See 1 more Smart Citation
“…on the SWNT sidewalls. [62,63,106,201,[231][232][233][234] This gives little or no change in electronic properties. [235] A number of polymers have recently been used to disperse SWNTs in non-aqueous media.…”
Section: Dispersion Of Nanotubes In Solventsmentioning
confidence: 99%
“…These include surfactants, [62,106,195,196,241] water-soluble polymers, [106,195,199,200,241,242] DNA, [63,64,243,244] polypeptides, [231][232][233] and cellulose derivatives. [201,234,245] …”
Section: Dispersion In Watermentioning
confidence: 99%
“…The MWNT and carboxymethyl cellulose solution was sonicated for 30 minutes to achieve good dispersion of the MWNTs in water, as shown in Figure 1A. It has been shown that carboxymethyl cellulose is an excellent surfactant allowing uniform dispersion of MWNTs in aqueous medium [25][26][27][28] . Figure 1A shows a diagrammatic representation of the entire process for the preparation of membranes.…”
Section: Preparation Of the Chitin Nanotube Filmsmentioning
confidence: 99%
“…Up to now, three methods have been used to prepare liquid crystalline CNTs: acid oxidation [24,25], polymer wrapping [26][27][28][29], and superacid protonation [30,31]. Acid oxidation is an efficient method of modifying the CNT surface by introducing functional groups [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…The process enables CNTs to be dispersed effectively in solvents without damage because the polymer allows them to disperse as individual units. A number of polymers have been investigated for the polymer wrapping method, such as conjugated polymers [26], amphiphilic block copolymers [27], polyelectrolytes [28], and biopolymers [29]. However, CNTs prepared by this method have inferior properties and limited applications due to intermolecular defects which remain after polymer wrapping.…”
Section: Introductionmentioning
confidence: 99%